PENGARUH MOTIVASI, PENDIDIKAN DAN PENEMPATAN TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PERUMAHAN RAKYAT KABUPATEN KERINCI: ELIYUSNADI, S.Kom., M.Si - Eliyusnadi (JURNAL ADMINISTRASI NUSANTARA, 2019)
The purpose of this research is 1. To know the Influence of Motivation, Education and Placement on Performance at Public Work Department and Housing of Kerinci Regency, 2. To know the amount of Influence of Motivation, Education and Placement on Performance of Public Works and Housing of Kerinci Regency Approach conducted in this study is a quantitative descriptive, because it describes the systematic facts and characteristics of objects and subjects are researched appropriately. The respondents in this study amounted to 90 people. This study uses data collection techniques that are field research and library research. The results showed that: Y = = 2,574 + 0,466X1 + 0,261X2 + 0,213X3. artimya that the variables Motivation, Education and Placement is improved then the performance of employees will increase. Result of calculation t calculate motivation 7,084, education 2,979 and placement 2,685 compared with t table 1,987 thus hence Ho refused and Ha accepted Mean that there are positive and significant influence between Motivation, Education and Placement to Performance at Department of Public Works and Housing of Kerinci Regency . Obtained f value counted 27,694 and compared with t table equal to 3,101 mean Motivation, Education and Placement effect on Employee Performance. While the magnitude of the influence of the independent variable to the devendent variable is 49.10% the remaining 50.90% influenced by other variables not included in this study.